Peer-to-Peer Accommodation Networks Pushing the boundaries - Dolnicar, Sara (Goodfellow Publishers, 2017)
Peer-to-Peer Accommodation Networks: Pushing the boundaries is the first book to provide an in-depth analysis of the business model of Airbnb, to discuss factors facilitating the transition of peer-to-peer networks from niche market to mainstream accommodation providers, and to predict that the next step of development for peer-to-peer accommodation networks will be to become online one-stop travel shops. Many other hot topics around peer-to-peer accommodation are discussed.